Polyphenols Extraction From Vegetable Wastes Using a Green and Sustainable Method - Doria, Enrico; Boncompagni, Eleonora; Marra, Antonio; Dossena, Maurizia; Verri, Manuela; Buonocore, Daniela (Frontiers in Sustainable Food Systems, 2021)
Food systems have the potential to support human health, respecting the environmental sustainability principles. Food sustainability, enclosed in the concept of environmental sustainability, involves different aspects, including the recycling of food waste derived from the agri-food production chain, the use of biotechnologies ensuring the sustainability of the recovery processes of bioactive compounds from food waste and, last but not least, the awareness of having to consume and waste less food. Food loss and waste is generated throughout the entire supply chain, from production to household utilization. The utilisation of agricultural wastes as an abundant, renewable and low-cost source for the production of high value-added products is currently explored. The bioactive compounds present in these sources have been proved to possess a wide range of biological activities; therefore, research is needed into the application of environmentally friendly traditional and advanced techniques with low production costs in the extraction, isolation and purification of phytochemical compounds from agricultural wastes in high yields and at maximal quality. Authors of this manuscript propose and discuss an innovative and sustainable extraction system of polyphenols from vegetable waste, based on an enzymatic pre-treatment coupled with a solid-liquid extraction by using a particular extractor (Naviglio Estrattore®). This extraction system, organic solvent free, allowed to extract relevant amount of polyphenols (flavonoids in particular) from several vegetable waste products.